Comparison of the Results of the Cervical Laminoplasty (Hattori's Method) and the Cervical Laminectomy - Saito, Yoshiaki; Kawai, Shinya; Kaneko, Kazuo; Taguchi, Toshihiko; Hashiguchi, Akira (Orthopedics & Traumatology, 2001)
The purpose of this paper is to compare radiological changes after cervical laminoplasty and laminectomy. The subjects were 78 patients with myelopathy caused by the cervical spondylosis or the ossification of the posterior longitudinal ligament in the cervical spine. 61 cases were treated using Z-shaped laminoplasty (Hattori's Method) and 16 using laminectomy. The average age at the time of surgery was 57, and the average follow-up period was 11 years and 2 months. The functional results were evaluated according to the Japanese Orthopaedic Association's scoring system. At the time of follow-up, the average recovery rate was 63% in the laminoplasty group, and 32% in the laminectomy group. In the laminoplasty group, the abnormality of alignment was greatly reduced in frequency and degree compared with the laminectomy group. The recovery rate was poor in patients with postoperative changes in the type of cervical spine curvature developed. Laminoplasty is considered to be superior to laminectomy in maintaining cervical alignment and preventing postoperative spinal deformities.